FORMATION OF COSTS AND CALCULATION OF THE COST OF MAINTENANCE OF IMPLEMENTED LABORATORY MEDICAL EQUIPMENT - E. Shapoval; I. Nesterovа (Вестник университета)
In article questions of sectoral planning of costs of warranty repair of medical equipment and the equipment and also the repair made upon termination of warranty periods, their similarity and distinctions are investigated. The cost of guarantee maintenance as the important indicator increasing prime cost of ready production is considered. The order of accounting of repair made by the organization at the expense of the buyer who is an additional source of income is considered. The indicators influencing formation of cost of the performed repair work on the profit of the enterprise are analyzed.